2020
DOI: 10.1002/acp.3743
|View full text |Cite
|
Sign up to set email alerts
|

Keyboard dynamics discrepancies between baseline and deceptive eyewitness narratives

Abstract: Information manipulation and cognitive load imposition make the production of deceptive narratives difficult. But little is known about the production of deception, and how its mechanisms may help distinguish truthful from deceitful narratives. This study focuses on the measurement of keystroke dynamics while typing truthful and deceptive eyewitness testimonies after a baseline assessment. While typing their narrative, some participants would undergo an auditory cognitive load. Results show that liars typed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…This accuracy is particularly interesting as it includes field data and experimental data. If experimental results compose most of these studies (e.g., Masip et al, 2012;Tomas et al, 2021c), other studies have focused on real-life data and shown similar results (Fornaciari and Poesio, 2013;Pérez-Rosas et al, 2015a, 2015b. For instance, an 84% accuracy rate in detecting misleading opinions was reached in a study using lexical (e.g., vocabulary richness) and syntactic (e.g., punctuation) stylometric features, as well as supervised learning methods (i.e., classification by algorithmic methods based on texts labeled as authentic or misleading, Shojaee et al, 2013).…”
Section: Main Results For Stylometric Deception Detection Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…This accuracy is particularly interesting as it includes field data and experimental data. If experimental results compose most of these studies (e.g., Masip et al, 2012;Tomas et al, 2021c), other studies have focused on real-life data and shown similar results (Fornaciari and Poesio, 2013;Pérez-Rosas et al, 2015a, 2015b. For instance, an 84% accuracy rate in detecting misleading opinions was reached in a study using lexical (e.g., vocabulary richness) and syntactic (e.g., punctuation) stylometric features, as well as supervised learning methods (i.e., classification by algorithmic methods based on texts labeled as authentic or misleading, Shojaee et al, 2013).…”
Section: Main Results For Stylometric Deception Detection Tasksmentioning
confidence: 99%
“…Indeed, lie detection from stylometric cues is a testable hypothesis: It is possible to determine, through human or algorithmic classification methods, whether the use of computational stylometry detects deception or not, in accordance with the falsifiability principle (Popper, 1959). Second, computational stylometry has been tested for its ability to detect deception with various tools and methods (e.g., for LIWC, see Ali and Levine, 2008;Fornaciari and Poesio, 2013;Newman et al, 2003;Tomas et al, 2021c; for named entity recognition, see Kleinberg et al, 2018; for morpho-syntactic labeling, see Banerjee and Chua, 2014; for n-grams, see Cagnina and Rosso, 2017;Hernández Fulsilier et al, 2015;Ott et al, 2013; for vector representations, see Nam et al, 2020; for BERT, see Barsever et al, 2020). Third, it has been the subject of over 20 peer-reviewed publications (e.g., Hauch et al, 2015;Forsyth and Anglim, 2020;Tomas et al, 2021a).…”
Section: Could Stylometry Be Used On the Field To Detect Deceit?mentioning
confidence: 99%
See 1 more Smart Citation
“…A study [213] included 283 subjects, while some of the few studies [102], [214]- [217] considered more than 300 subjects. A recent study [218] used GPower for estimating sample size. In KD research, most of the studies included patterns collected from college or university students, teachers, support staff, etc.…”
Section: F Subject Size and Subject Selectionmentioning
confidence: 99%
“…Yet, this approach appears controversial and mostly ineffective (Vrij, 2016;Caso et al, 2019a,b). Efforts have been made to improve its efficacy (Palena et al, 2019;Verigin et al, 2020;Tomas et al, 2021b), and a recent study has questioned its relevance, without rejecting it either (Tomas et al, 2021a). Furthermore, although the baseline attempts to deal with personal characteristics, almost all research studies in investigative interviewing used a variable-centred approach (Magnusson, 1992(Magnusson, , 1998.…”
Section: Account For Interpersonal Differences and Intersubjectivitymentioning
confidence: 99%